Ubrogepant Is Not Associated With Clinically Meaningful Elevations of Alanine Aminotransferase in Healthy Adult Males - Ankrom, Wendy (Clin Transl Sci, 2020)
Ubrogepant is a novel, oral calcitonin gene‐related peptide (CGRP) receptor antagonist intended for the acute treatment of migraine attacks. Ubrogepant has a chemical structure distinct from previous small‐molecule CGRP receptor antagonists that were associated with elevated serum alanine aminotransferase (ALT) in clinical trials. Here, we report overall and hepatic safety data from two placebo‐controlled phase I trials of ubrogepant, spray‐dried oral compressed tablet (SD‐OCT) in healthy male volunteers. Trial A was a pharmacokinetic (PK) trial of single (100–400 mg) and multiple (40–400 mg) ascending doses. Trial B was a dedicated hepatic safety trial assessing daily use of ubrogepant 150 mg for 28 days. Serum ALT (as hepatotoxicity biomarker) and PK data are reported. Ubrogepant was well‐tolerated in both trials, with a low incidence of adverse events that did not differ greatly from placebo. Changes in mean ALT levels were minimal and similar to placebo. Over 28 days of treatment, the mean percentage change in ALT from baseline was < 5% at all time points. No participant in either trial demonstrated ALT ≥ 3× upper limit of normal at any time. Ubrogepant SD‐OCT demonstrated linear PK appropriate for acute treatment of migraine, with rapid uptake (time of maximum plasma concentration (t(max)): 2–3 hours) and no accumulation with daily use. Overall, there was no evidence of ubrogepant‐associated hepatotoxicity with daily doses up to 400 mg for 10 days or with daily ubrogepant 150 mg for 28 days. Supratherapeutic dosing is a useful strategy for characterizing hepatic safety in early drug development.